2022
DOI: 10.1007/s11356-022-20831-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate in groundwater and agricultural products: intake and risk assessment in northeastern Iran

Abstract: The suitability of groundwater and agricultural products for human consumption requires determining levels and assessing the health risks associated with potential pollutants. Here, particularly pollution with nitrate still remains a challenge, especially for those urban areas suffering from insufficient sewage collection systems, resulting in contaminating soil, endangering food safety, and deteriorating drinking water quality. In the present study, nitrate concentrations in the commonly consumed fruit and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 88 publications
1
6
1
Order By: Relevance
“…These studies further confirm our findings about the concern on high levels of nitrate in some regions of Tehran–Karaj aquifer. Using the groundwater samples taken in west of Tehran city in 2016, Shirazi et al 77 reported no concern about the elevated concentration of nitrate in this region—a finding that is in-line with our results as shown in Fig. 4 .…”
Section: Discussionsupporting
confidence: 92%
“…These studies further confirm our findings about the concern on high levels of nitrate in some regions of Tehran–Karaj aquifer. Using the groundwater samples taken in west of Tehran city in 2016, Shirazi et al 77 reported no concern about the elevated concentration of nitrate in this region—a finding that is in-line with our results as shown in Fig. 4 .…”
Section: Discussionsupporting
confidence: 92%
“…This characteristic suggests that when Cl − is higher than the NO3 − /Cl − ratio, nitrate pollution is related to domestic effluent and sewage, whereas reverse ratios are typically related to precipitation/fertilizers [54]. The approach A strong correlation between nitrate and other anions (such as chloride, phosphate, and sulfate) was found in earlier studies [42], suggesting that these pollutants come from the same source such as sewage water leaks into the groundwater. Elevated nitrate concentrations in tap water could be related to domestic sewage due to the poor condition of water pipes and insufficient wastewater treatment [40,43].…”
Section: Source Identification Of Nitratementioning
confidence: 89%
“…Numerous studies [18,20,51,52] have used stable isotope analysis, such as dual nitrogen and oxygen isotope ratios of nitrate, to identify nitrate pollution sources. Also, the sources of nitrate contamination in water have been found using relationships between nitrate, nitrite, ammonium, and chloride [42,53]. According to Liu et al [54], chloride is not affected by physicochemical or microbiological processes that take place in groundwater, making it useful as a sewage impact indicator.…”
Section: Source Identification Of Nitratementioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli (E. coli) was used as an indicator of groundwater quality as its presence indicates fecal contamination (Febriarta, 2020;Sejati, 2020;Zendehbad, Mostaghelchi, Mojganfar, Cepuder, & Loiskandl, 2022). Table 5 shows the results of the E. coli test for groundwater samples with the standards for E. coli bacteria for sanitation hygiene purposes are explained in the rightmost column in the table.…”
Section: Groundwater Condition Based On Biological Parametermentioning
confidence: 99%